PERAN PENDIDIKAN USIA DINI BAGI PERKEMBANGAN KOGNITIF ANAK DALAM MENGIKUTIPELAJARAN DI SEKOLAH DASAR INPRES WEKAKEU, DESA EKIN, KECAMATAN LAMAKNEN SELATAN, KABUPATEN BELU - Aluk, Magdalena; Kase, Emanuel B.S; Rusae, Yohanes (Pastoralia Jurnal Penelitian Dosen, 2020)
The basic reason for the writer to choose this title is the concern and expectation of the writer on Wekakeu Inpres Elementary School students' understanding of children's cognitive development or abilities so minimal and less active in following lessons in class. Because many children do not attend early education or do not pass early education. The author wants to find out thenumber of children who took early education and who did not attend early education. What factors influence these children so they are not active in class. The focus of the study in this goal is to explore the extent of children's understanding of early education for children's cognitive development with interview techniques. The formulation of the problem to be raised is how to describe the cognitive development of children in Wekakeu Inpres Elementary School, factors that affect children's cognitive development in following thelessons and what efforts are made to improve children's cognitive development. The purpose of the research is to answer the formulation of the problem raised. This research is intended for Wekakeu Inpres Elementary School Children, institutions and for parents. The term limits are limited to an explanation of the terms used in the title. The results showed that the wekakeu inpres elementary school students did not understand the role of early education for children's cognitive development because of internal and external factors. For this reason, efforts must be made that students have the will to overcome internal and externalfactors